Modifikasi Garis Singgung Untuk Mempercepat Iterasi Pada Metode Newton Raphson - Maxrizal, Maxrizal (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
The Newton-Raphson method is one of the methods to find solutions or roots of nonlinear equations. This method converges faster than other methods and is more effective in finding doubles. In this study, it will be shown that the Newton-Raphson modification uses modifications to the tangent equation. The results show that for every nth iteration, the speed difference of Newton Raphson modification is __. Furthermore, the convergence of Newton Raphson is __, and for Newton Raphson modification is __.